Development of an Academic Position Application System for the Faculty of Science, Prince of Songkla University - Theparun, Siriporn; Wanno, Wanchai; Sae Ui, Phusit (Journal of Information and Learning [JIL], 2024)
This research aims to develop a system for academic position applications, evaluate its effectiveness, and to assess user satisfaction with the online academic position application system at the Faculty of Science, Prince of Songkla University. The research population consisted of 70 faculty members from the Faculty of Science, Prince of Songkla University, who applied for academic positions between 2022 and 2024. Data were collected using a questionnaire, with a reliability coefficient of 0.67. The statistics used for data analysis included frequency, percentage, mean, standard deviation, and content analysis. The research findings reveal that the information system possesses comprehensive features for data entry, retrieval, and summarization, in accordance with the format required by the Office of the Civil Service Commission (OCSC) 03, which stipulates that applicants for academic positions must provide detailed information. The application system includes three user groups: applicants for academic positions, department heads, and system administrators. The system collects data by retrieving personal information, educational background, work history, teaching workload for the past three years, and academic achievements. The data will then be sent to the department head for review and approval along with the selection of qualified experts. Subsequently, the data are forwarded to the staff for accuracy verification. The system then generates a report to be submitted to the dean and forwarded to the university for further processing according to the next steps. The effectiveness evaluation of the online academic position application system, based on lean principles, indicates that the system effectively reduces waste in the application process, can shorten the processing time by up to 31 days, and decreases paper usage.